Pengaruh Cerita Anak Bergambar Terhadap Kemampuan Berbicara Siswa Kelas 2 SD Negeri Gugus 1 Kota Bengkulu - Maria Veronica Oktaviani; Abdul Muktadir; Pebrian Tarmizi (JURIDIKDAS, 2020)
The purpose of this study is to determine the effect of illustration children's stories on students' speaking abilities. This research is quantitative. The method used is a quasi experimental design with the matching only posttest group design. The population in this study was the cluster 1 SD Negeri Bengkulu City. The sampling technique uses cluster random sampling. The sample in this study was class 2B SD Negeri 1 Bengkulu City as an experimental class and class 2B SD Negeri 7 Bengkulu City as a control class. The instrument used in the study was the observation sheet of speaking ability. Data collection techniques based on posttest results using observation sheets. Data analysis techniques are by looking for means (mean) and variance, normality test with the Liliefors formula, homogeneity test and t-test. Based on the results of the normality test that the data are normally distributed. The experimental class obtained a speaking ability score with a percentage of 78.1% in the very good criteria, while the control class spoke the ability to speak with a percentage of 64.6% in the good criteria. The t-test results showed that Ha was accepted and Ho was rejected because tcount > ttable with tcount 13,6 and ttable 12,8 which means that there was an influence of children's picture stories on students' speaking abilities